USE OF TECHNOLOGY IN TEACHING ENGLISH - Pratiwi, Ayu; Pratiwi, Elsa; Chantika, Faradila; Putri, Hamida; Nengsih, Resti Aulia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
In language coaching and gaining knowledge of, we've got loads to select from the sector of generation: audio, TV, CD Rom, Computers, C.A.L.L., the Internet, Electronic Dictionary, Email, Blogs and Audio Cassettes, Power Point, Videos, DVD’s or VCD’s. Technology has modified the dynamics of diverse industries, and has additionally encouraged the the manner human beings engage and paintings withinside the society. This speedy growing and improvement of statistics era has supplied a higher sample to discover the brand new coaching version. As a end result era performs a totally vital position in English coaching. Using multimedia to create a context to train English has its particular advantages. The instructors can have interaction the freshmen to grow to be professional at English Language through the usage of the revolutionary ELT strategies like English songs, movie, clippings, dramatics, advertisements, sports activities commentaries and plenty of extra. This paper stresses at the want to make English language training smooth and exciting thru revolutionary ELT techniquesby using a scope review study methodology, which is a literature review process between new theories and ideas, so this paper talk about definition and development of technology, use of generation in coaching English, the boom of elt via generation, and advantages of the use of generation in the classroom.